A Pd−H/Isothiourea Cooperative Catalysis Approach to anti‐Aldol Motifs: Enantioselective α‐Alkylation of Esters with Oxyallenes. Issue 25 (20th April 2022) - Lin, Hua‐Chen; Knox, Gary J.; Pearson, Colin M.; Yang, Chao; Carta, Veronica; Snaddon, Thomas N.
Abstract: The biological and therapeutic significance of natural products is a powerful impetus for the development of efficient methods to facilitate their construction. Accordingly, and reflecting the prevalence of β‐oxy‐carbonyl motifs, a sophisticated arsenal of aldol‐based strategies has evolved that is contingent on the generation of single enolate isomers. Since this has the potential to compromise efficiency in reagent‐based paradigms, direct catalysis‐based solutions would be enabling. To complement the array of substrate‐based strategies, and regulate enolate geometry at the catalyst level, a direct catalytic alkylation of esters with oxyallenes has been developed. Synergizing metal hydride reactivity with Lewis base catalysis has resulted in a broad reaction scope with useful levels of stereocontrol (up to >99 % ee ). Facile derivatization of these ambiphilic linchpins is demonstrated, providing access to high‐value vicinal stereocenter‐containing motifs, including 1, 2‐amino alcohols. Abstract : Cooperation between isothiourea and Pd catalysts enables the preparation of anti ‐aldol products via enantioselective alkylation of esters with oxyallenes. Key to the successful development of this method was the recognition that Pd−H intermediates could be leveraged within this cooperative framework giving access to oxygen‐substituted π(allyl)Pd intermediates. Preliminary deuterium‐tracking experiments support the proposed reaction pathway.